Performance-optimized microstrip coupled VCOs for 40-GHz and 43-GHz OC-768 optical transmission. - Shaeffer, D.K (IEEE Journal of solid state circuits)
In this paper, we present 40- and 43-GHz voltage-controlled oscillators (VCOs) for use in SONET/SDH optical transmission systems operating at OC-768 rates. SONET system jitter requirements are explained, as are methods for achieving the requisite performance in manufacturable oscillators. We describe in detail a technique for using quadrature-coupled VCOs to achieve a fundamental improvement in jitter power performance. The 40-GHz oscillator has a tuning range of 5 GHz, a single-sideband phase-noise power spectral density of -99 dBc/Hz at 1-MHz offset from the carrier, and consumes 207 mW in the oscillator core. Total power consumption is 363 mW (including biasing and output buffers) from a 3-V supply. The oscillator occupies 0.189 mm2 of die area and is implemented in a 120-GHz fT SiGe BiCMOS process.